Agni depicted holding a pointed spoon and a pushpa - Temples of India Project Team (Jio Institute, 2024)
Agni, the guardian of the southeast direction, is depicted holding a pointed spoon and a pushpa (flower) in his upper hands. His lower hands and the face of his vahana (mount) are broken. He wears a jatamukuta (crown of matted hair) and has a beard.